Upwelling study of chlorophyll a content in phytoplankton of the western Caspian in 2017 based on remote sensing data - N. O. Guseynova; A. A. Bagomaev; L. Sh. Akhmedova; B. M. Kuramagomedov (Юг России: экология, развитие)
Aim. Study of upwelling based on spatio‐temporal variability of chlorophyll a concentration in the western part of the Caspian Sea in 2017 based on space survey images.Materials and methods. Space images were obtained from the specialized centers of Ocean Color NASA, Earth Science Data Systems NASA and SATIN. Remote sensing data was processed using SeaDAS and ArcGIS programmes. Ground data were obtained from the Unified State System of Information on the Situation in the World Ocean (ESIMO). ESIMO is an inter‐agency information system designed to integrate data and services of marine systems of Russia and to provide integrated information support to maritime activities of the Russian Federation. The database was created in ArcGIS and maps compiled accordingly.Results. The first upwelling occurred on 9‐17 June 2017. The minimum water temperature registered in the Makhachkala region was 14°C with an increase in salinity to 12‰, over an area of 1.500 km2. There was an increase in the content of dissolved oxygen up to 9.70 mg/l and a pH of 8.64 was recorded. At first, the concentration of chlorophyll a was more than 10 mg/m3, then it decreased to 2.5 m/m3, while at the same time the area of distribution of chlorophyll with this indicator significantly increased. For the coastal strip, the chlorophyll index was 5 mg/m3. The second upwelling of medium intensity was from 19 June to 1 July 1 2017 with a minimum of t = 17.9°C with an increase in salinity of 1‰. The surface area was 454 km2. The concentration of chlorophyll a increased from 4 to 8‐12 mg/m3, reaching 23 mg/m3 on 24 June. The third case of upwelling was recorded from 26 August to 1 September 2017 and was characterized by a decrease in water temperature by 7.4°C (near the coast by 17.1°C). The average salinity increase was 0.32‰, while the O2 concentration was 8 mg/l and the water area 500 km2. A sharp increase in the area and concentration of chlorophyll was observed on 29 August 2017. Subsequently, the concentration of chlorophyll throughout the entire water area was evenly distributed in the range of 1‐5 mg/m3.Conclusion. The Caspian Sea is characterized by spatial heterogeneity of oceanological parameters, which can be recorded based on the results of processing satellite images and their verification using ground data. In the western part of the sea, the upwelling is periodic and of different scales. In total, on the basis of the capabilities of multifactor geoinformation modeling, 3 upwellings were identified and confirmed using satellite data.